The relationship between Maximal Bite Forces and Dental Status in Shipbuilders - Živko-Babić, Jasenka; Tomljenović, Ana Marija; Komar, Dragutin Jakovac, Marko; Carek, Andreja (2006)
Technological advancement in the industry and etire field of human development provide a better quality of work conditions and environment. On the other hand, pollution has became more dangerous for human health. The aim of this study was to estimate dental status and to correlate it with maximal bite forces and the pressure of the finger and thumb.
Projekt MZOS
ENG